Respuesta :

For this case we have the following expression:

[tex]\sqrt [4] {11} \sqrt [4] {10}[/tex]

For radical properties, we have to:

[tex]\sqrt [a] {b} \sqrt [a] {c} = \sqrt [a] {bc}[/tex]

Therefore, making use of the definition, we can rewrite the given expression.

We have then:

[tex]\sqrt [4] {11} \sqrt [4] {10} = \sqrt [4] {(11) (10)}\\\sqrt [4] {11} \sqrt [4] {10} = \sqrt [4] {110}[/tex]

Answer:

The equivalent expression is given by:

[tex]\sqrt [4] {11} \sqrt [4] {10} = \sqrt [4] {110}[/tex]

Option D